Perinatal adversities in tuberous sclerosis complex: Determinants and neurodevelopmental outcomes. (2nd April 2022) - Zhang, Alexa X. D.; Liang, Holan; McEwen, Fiona S.; Tye, Charlotte; Woodhouse, Emma; Underwood, Lisa; Shephard, Elizabeth; Sheerin, Fintan; Bolton, Patrick F.
Abstract: Aim: To examine the association between perinatal adversities and neurodevelopmental outcome in tuberous sclerosis complex (TSC). Method: The Tuberous Sclerosis 2000 study is a prospective, longitudinal UK study of TSC. In phase 1, mutation type, TSC family history, tuber characteristics, presence of cardiac rhabdomyomas, seizure characteristics, and intellectual ability were assessed in 125 children affected with TSC (64 females, 61 males; median age 39mo, range 4–254). In phase 2, 88 participants (49 females, 39 males; median age 148mo, range 93–323) were assessed for neurodevelopmental outcomes including intellectual ability, autism spectrum disorder, and attention‐deficit/hyperactivity disorder. Perinatal histories of 88 participants with TSC and 80 unaffected siblings were collected retrospectively using the Obstetric Enquiry Schedule and coded with a modified Gillberg Optimality Scale to measure levels of perinatal adversity. Data were analysed using Mann–Whitney U tests, Spearman's rank correlation, and linear regression with robust standard errors. Results: Children with familial TSC experienced significantly greater perinatal adversity than unaffected siblings. Perinatal adversity was higher in children with TSC‐affected mothers than those with unaffected mothers. There was no significant association between perinatal adversities and neurodevelopmental outcomes after controlling for confounders. Interpretation: Maternal TSC is a significant marker of elevated perinatal risk in addition to risks incurred by fetal genotype. Pregnancies complicated by maternal or fetal TSC require higher vigilance, and mechanisms underlying increased perinatal adversity require further research. What this paper adds: Higher perinatal adversity is associated with familial tuberous sclerosis complex (TSC). Maternal TSC was associated with higher frequencies of several perinatal risk markers. Paternal TSC was not associated with higher levels of perinatal adversity. Perinatal adversity levels in TSC1 and TSC2 subgroups did not differ significantly. Perinatal adversities were not associated with neurodevelopmental outcomes. What this paper adds: Higher perinatal adversity is associated with familial tuberous sclerosis complex (TSC). Maternal TSC was associated with higher frequencies of several perinatal risk markers. Paternal TSC was not associated with higher levels of perinatal adversity. Perinatal adversity levels in TSC1 and TSC2 subgroups did not differ significantly. Perinatal adversities were not associated with neurodevelopmental outcomes. This original article is commented on by Franz on pages 1184–1185 of this issue.